Informal Transnational Police-to-Police Information Sharing: Its Structure and Reform - Walton, Michael Robert (2014)
This thesis examines the informal sharing of information and cooperation between police agencies across international borders, and how it is or should be informed by international human rights law. The author looks at how intelligence-led policing theory has affected transnational policing. A distinction is made between police actions made on domestic soil that have adverse consequences abroad and police actions made on foreign soil that have adverse consequences. The first category of cases is firmly within jurisdiction and covered by domestic and international legal obligations. The second category of cases introduces the concept of the extraterritorial application of international human rights instruments. The theory is illustrated by the case studies of the Bali Nine and of Maher Arar. Finally the author suggests methods of best practice for transnational information sharing and suggests that all government agencies should follow these rules